Impact of Motivations for Volunteering on Well-Being Among OT and Health Sciences Students...American Occupational Therapy Association, INSPIRE Conference, March 31-April 3, 2022, San Antonio, Texas. - Naber, Allison (American Journal of Occupational Therapy)
Date Presented 04/02/2022 This cross-sectional survey study used the RAND 36-Item Short Form Survey and Volunteer Function Inventory to explore relationships between motivations for volunteering and perceived well-being. A majority of participants were health sciences and OT students who had volunteered in the past year. The findings add to volunteerism literature and facilitate the organization of volunteer opportunities with students in OT and health sciences-related programs. Primary Author and Speaker: Allison Naber